Jaundice due to carbimazole. Issue 11 (November 1975) - Lunzer, M; Huang, S N; Ginsburg, J; Ahmed, M; Sherlock, S
Abstract : On three occasions, a 63 year old housewife with hyperthyroidism developed a reaction which included fever, pruritus, malaise, and, on one occasion, jaundice one to 17 days after taking carbimazole. Challenge with carbimazole was followed within 12 hours by abdominal pain, pruritis, and increased serum transaminase levels. Light microscopy of a liver biopsy showed increase of portal zone cellularity over the control and the electron microscopy revealed fine structural changes compatible with drug-related liver injury.